Analisis Faktor Sosiodemografi yang Mempengaruhi Beban Pengasuhan Keluarga pada Lansia dengan Hipertensi - Yusuf , Nur Ayun R; Sartika, Sartika; Purwanto, Erwin; Maryadi, Maryadi (Mando Care Jurnal, 2025)
Hypertension is the leading cause of premature death globally, with a prevalence of approximately 1.5 billion cases among adults worldwide. This condition affects not only patients, but also their family members who care for them. This study aims to analyze the relationship between sociodemographic factors (occupation, income, family relationships) and caregiving characteristics (length of care) with the burden of family caregiving for elderly people with hypertension in the Kabila Community Health Center working area. The study used a quantitative cross-sectional design involving 107 primary caregivers selected through purposive sampling. Inclusion criteria included caregivers aged ≥18 years, living with the elderly person, and able to communicate well; exclusion criteria were caregivers with cognitive impairment or unable to complete the questionnaire independently. The instrument used was the modified 22-item Zarit Burden Interview (ZBI), and data analysis was performed using the Chi-Square test with a significance level of p<0.05. The results showed that 57% of respondents experienced a light burden, and all independent variables showed a significant relationship with the burden of caregiving: occupation (p=0.000), income (p=0.000), family relationships (p=0.002), and duration of care (p=0.005). This study concluded that several sociodemographic factors and care characteristics were significantly associated with the burden of family caregiving, thus requiring more comprehensive family-based health services to assist caregivers of elderly people with hypertension.